Built Women in Men's Paradises: A Critical Analysis of the Garden of Eden Narrative and Alex Garland's Ex Machina. - Chapman, Cynthia R. (Journal of Religion & Popular Culture, 2022)
Bringing the biblical story of the Garden of Eden (Genesis 2-3) into conversation with Alex Garland's 2014 film Ex Machina, this paper examines and compares the male-scribed nature of paradise stories that describe the "building" of woman-creatures. From ancient Judean scribes to modern film-makers and computer coders, male-guarded forms of literacy enabled and continue to enable storytelling and world-building. A comparison of the accounts of the creation of Eve of the Garden with Ava of Ex Machina highlights that male control over literacy more generally and creation accounts more specifically yields diminished woman-creatures designed to serve the specific needs of men in male-imagined paradise settings. Although separated by millennia, ancient Judean scribes and modern computer programmers have imagined and built woman-creatures with a limited set of functions and programmed routines that include providing help, serving as a companion, and heterosexual receptivity.